Impact of Covid-19 Pandemic on Ministry of Religious Affairs Policy in Entrepreneurial Development of Pondok Pesantren - Fatmawati Fatmawati; Ade Sofyan Mulazid (Jurnal Madania, 2021)
This study aims to analyze the impact of the Covid-19 pandemic on the Ministry of Religious Affairs policies in the development of entrepreneurial pondok pesantren (Islamic boarding schools). This research method used a qualitative descriptive approach. The primary data source comes from interviews and activity reports obtained directly from the office of the Directorate of Diniyah Education and Pondok Pesantren of the Ministry of Religious Affairs and other relevant documentation. Data analysis techniques used descriptive qualitative analysis, intended to find out the social reality of the Ministry of Religious Affairs as policymakers of entrepreneurial pondok pesantren assistance programs affected by the Covid-19 pandemic that was constructed by the mass media through advertising creators and newsmakers. The results showed that the Covid-19 pandemic also affected the economic life of the Islamic boarding schools. Hence, policies and strategic measures were needed to develope vocational life skill education programs designed to support the sustainable progress of business units at the schools. The entrepreneurial and vocational life kills of Islamic boarding schools movement initiated by the Ministry of Religious Affairs in collaboration with Bank Indonesia has broader implications on aspects of the reach of ummah economic empowerment and the economic independence of the Islamic boarding schools improved the welfare of the surrounding community.